Antagonistic test of Penicillium sp. against the pathogen Colletotrichum sp. causing anthracnose disease in-vitro - Noviana Budianti Kartikasari; Hanik Faizah; Eko Teguh Pribadi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2026)
Anthracnose is a type of plant diseases caused by the pathogen Colletotrichum sp. Anthracnose disease can infect all plant organs, such as leaves, branches, twigs, and fruits. The initial symptoms of anthracnose disease are dry and dark brown spots. The process of anthracnose disease spread is so fast that it can reduce agricultural productivity. One alternative to environmentally friendly plant control is the use of biological control agent. Penicillium sp. is one of the fungi used as a biological control agent. This study aims to determine the antagonistic ability of Penicillium sp. against the pathogen Colletotrichum sp. causing anthracnose disease in-vitro. This research is classified as experimental research using the dual culture method. This research consists of two treatments and two replications. The control treatment was conducted using only the pathogen Colletotrichum sp. This research was conducted for 7 days at a temperature of 25℃ using PDA medium. The observation process was carried out by measuring the diameter of the control and treatment pathogens for 7 days. Data analysis in this study was conducted using descriptive statistics to determine the mean and standard deviation of a treatment. The results show that Penicillium sp. can inhibit the pathogen Colletotrichum sp. with the highest inhibition percentage on the 7th day after inoculation of 49.14 ± SD 2.39%, which falls within the medium criteria. The inhibition mechanism of Penicillium sp. against the pathogen Colletotrichum sp. occurs through competition and antibiosis.